Task conflict in the Stroop task: When Stroop interference decreases as Stroop facilitation increases in a low task conflict context - Parris, Benjamin A. (Frontiers in Psychology, 2014)
In the present study participants completed two blocks of the Stroop task, one in which the Response-Stimulus Interval (RSI) was 3500ms and one in which RSI was 200ms. It was expected that, in line with previous research, the shorter RSI would induce a low Task Conflict context by increasing focus on the colour identification goal in the Stroop task. Based on previous research showing the role of Task Conflict in the presence or absence Stroop facilitation, this was expected to lead to the novel finding of an increase in facilitation and simultaneous decrease in interference. Such a finding would be problematic for models of Stroop effects that predict these indices of performance should be affected in tandem. A crossover interaction is reported supporting these predictions. As predicted, the shorter RSI resulted in incongruent and congruent trial RTs decreasing relative to a static neutral baseline condition; hence interference decreased as facilitation increased. An explanatory model (expanding on the work of Goldfarb, Henik and colleagues) is presented that: 1) Shows how under certain conditions the predictions from single mechanism models hold true (i.e. when Task conflict is held constant); 2) Shows how it is possible that interference can be affected by an experimental manipulation that leaves facilitation apparently untouched and; 3) Predicts that facilitation cannot be independently affected by an experimental manipulation.